Effect of Tapentadol on Splenic Cytokine Production in Mice. (March 2017) - Franchi, Silvia; Amodeo, Giada; Gandolla, Marta; Moschetti, Giorgia; Panerai, Alberto Emilio; Sacerdote, Paola
Abstract : BACKGROUND: Opioid drugs affect immunity, but not all opioid drugs share the same immunomodulatory properties. Tapentadol is an analgesic drug with a dual synergistic mechanism of action: µ-opioid receptor agonism and noradrenaline reuptake inhibition. Weaker µ-opioid receptor agonism combined with noradrenaline reuptake inhibition results in potent analgesia with reduced opioid side effects. We evaluated the impact of tapentadol on splenic cytokine in normal and in hyperalgesia/allodynia mice, comparing it with morphine and reboxetine, a noradrenaline reuptake inhibitor. METHODS: Tapentadol, reboxetine, and morphine were injected subcutaneously into naïve and mice that underwent sciatic nerve chronic constriction injury, and their effect on splenic cytokines (interferon-γ [IFN-γ], interleukin [IL]-2, IL-10, and IL-4) was measured by enzyme-linked immunosorbent assay after acute or chronic treatment. Nociceptive thresholds, thermal hyperalgesia, and allodynia also were assessed. Data were analyzed with 2-way analysis of variance (behavior) or 1-way analysis of variance (cytokines) followed by Bonferroni post hoc test. RESULTS: Primary outcomes of our study were the effects of drugs on splenic cytokines. Our data indicate that acute tapentadol did not modify cytokine production in comparison with animals that received saline, whereas morphine suppressed all the cytokines: saline versus morphine 10 mg/kg (mean difference [MD], 95% confidence interval [CI]: IFN-γ = 12, 400 [7760, 17, 040], P < .001; IL-2 = 216.2 [47.69, 384.7], P < .01; IL-10 = 868 [523.7, 1212], P < .001; and IL-4 = 17.26 [10.32, 24.20], P < .001). A significant difference also was present between morphine and tapentadol (morphine 10 mg/kg versus tapentadol 20 mg/kg: MD [95% CI]: IFN-γ = −11, 600 [−16, 240, −6960], P < .001; IL-2 = −334.2 [−502.7, −165.7], P < .001; IL-10 = −959 [−1303, −614.7], P < .001; IL-4 = −18.66 [−25.60, −11.72], P < .001). When chronically injected for 7 days, tapentadol and reboxetine did not significantly affect cytokines when compared with saline-treated animals. The immunoprofile of tapentadol was different from that of morphine also in mice that were in a condition of neuropathic pain. All cytokines appeared significantly decreased in mice that received a chronic constriction injury in comparison with sham animals but, after 7 days of treatment, with a similar antihyperalgesic profile, IL-10 and IL-4 were significantly increased in tapentadol and reboxetine animals in comparison with morphine mice (morphine versus tapentadol: MD [95% CI], IL-10 = −926.4 [−1664, −188.5], P < .01; IL-4 = −8.15 [−12.46, −3.84], P < .001). CONCLUSIONS: Acute and chronic tapentadol seem to be protective of splenic cytokines in contrast with morphine, which exerts a generalized suppression on all cytokines. Abstract : Published ahead of print December 16, 2016.